Postoperative Adjuvant Chemotherapy Regimen of CAPOX Combined With Ninjin'yoeito in an Elderly Patient With Stage III Colon Cancer: A Case Report - Aomatsu, Naoki; Uchima, Yasutake; Tsujio, Gen; Miyamoto, Yoshinari; Okada, Takuma; Kurihara, Shigeaki; Matsutani, Shinji; Hirakawa, Toshiki; Iwauchi, Takehiko; Morimoto, Junya; Yamagata, Shigehito; Nakazawa, Kazunori; et al. (Frontiers in Nutrition, 2020)
We report the successful management of stage III colon cancer in an elderly patient who received an adjuvant chemotherapy regimen of capecitabine plus oxaliplatin (CAPOX) with the Japanese kampo medicine ninjin'yoeito (NYT). A 75-year-old woman with a medical history of hypertension presented at another institution with fecal occult blood, and a colonoscopy that showed a type II tumor in the sigmoid colon. She was referred to our hospital for tumor resection, where colonoscopy confirmed the location of the type II tumor in the sigmoid colon. Histopathology of the biopsy specimen indicated a moderately differentiated tubular adenocarcinoma. Enhanced computed tomography of the thorax and abdomen indicated thickening of the sigmoid colon wall. Regional lymph node metastasis was suspected, but distant metastasis was not indicated. A blood examination revealed an elevated carcinoembryonic antigen (CEA) concentration (32.7 ng/ml). Following a diagnosis of cancer of the sigmoid colon, clinical stage IIIb [cT4a, N1b, M0], a laparoscopic sigmoid colectomy was performed without complications. The postoperative histopathological examination revealed a moderately differentiated to mucinous adenocarcinoma. Three of 16 retrieved lymph nodes contained malignant cells. The final tumor classification was Stage IIIb [pT4a, pN1b, M0]. The patient recovered uneventfully, and was discharged 10 days after surgery with a recommendation for adjuvant chemotherapy with CAPOX starting 4 weeks after surgery. The patient also received 7.5 g of NYT daily throughout the adjuvant chemotherapy course. She did not report any loss of appetite, general fatigue, peripheral neuropathy, neutropenia, or febrile neutropenia. During a 1-year postoperative follow-up, she has not experienced any recurrence. We conclude that NYT might be useful for reducing the adverse effects of anticancer therapy, particularly in elderly patients.